Effect of Nitrogen and Mulches on the Yield and Economics of Chinese Cabbage (Brassica campestris var. Pekinensis) - Easmin, D; Akand, MH; Islam, MJ (Progressive Agriculture, 2013)
An experiment was conducted at the Horticulture Farm of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during the period from October 2005 to December 2005 to study the effect of nitrogen and mulching on the growth and yield of Chinese cabbage. The highest fresh weight of head (2.43 kg) was recorded in N3 (250 kg N/ha) on the other hand the lowest fresh weight (1.57 kg) was recorded in N0 (control). The maximum thickness and diameter of head (25.18 and 17.06 cm) of Chinese cabbage was recorded in N3 (250 kg N/ha) and the minimum thickness and diameter of head (18.98 and 14.21 cm) was recorded in N0 (control). The highest marketable yield per hectare of Chinese cabbage (120.06 ton) was recorded in N3 (250 kg N/ha) and the lowest yield (67.90 ton) was recorded in N0 (control). The highest fresh weight of head/plant of Chinese cabbage (2.44kg) was recorded in M1 (black polythene) and the lowest fresh weight of head (1.72kg) was recorded in M0 (control). The maximum thickness and diameter of head of Chinese cabbage (24.74 and 16.86 cm) was recorded in M1 (black polythene) and the minimum thickness and diameter of head (18.98 and 15.10 cm) was recorded in M0 (Control). The highest marketable yield per hectare of Chinese cabbage (123.27 ton) was recorded in M1 (black polythene) and the lowest yield (76.51 ton) was recorded in M0 (control). In and every case maximum growth and yield contributing characters and yield was observed in N3M1 (250 kg N + black polythene) and the reverse result was recorded in N0M0 (control). In the combination of different doses of nitrogenous fertilizer and different mulches highest benefit cost ratio (3.56) was attained from the treatment combination N3M1 (250 kg N + black polythene) and the lowest (1.22) was obtained in N0M0 (Control). DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16855 Progress. Agric. 20(1 & 2): 79 84, 2009